Slowenischer Weg? Die Politik der „ Europäisierung" in Europas südöstlicher Peripherie - Lindstrom, Nicole; Piroska, Dora (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
The paper starts with an overview of competing theoretical approaches to understanding Europeanization of Central and East European applicant states. lt is suggested that instead of seeing the process as strictly "top-down," we must investigate the ways in which the common pressures and constraints of Europeanization are processed and responded to in particular local contexts. In the main section the paper is focussed on the case of Slovenia in order to examine how common pressures impinge upon, challenge or reinforce national ’models’ and practices, in particular two "sites of Europeanization" are examined: the restructuring of the Slovenian banking sector and recent political turmoil around the privatization of a local Slovene brewery. The authors suggest through these cases how the process of Europeanization operates not only in the political sphere, but also involves contentious debates in the public sphere.